Direct visualization of the drug loading of single DNA origami nanostructures by AFM-IR nanospectroscopy. Issue 32 (21st July 2022) - Hanke, Marcel; Grundmeier, Guido; Keller, Adrian
Abstract : Chemical imaging of methylene blue (MB)-loaded DNA origami by AFM-IR nanospectroscopy is demonstrated. MB-specific IR absorption correlates well with the DNA origami topography and scales both with loading concentration and DNA origami thickness. Abstract : The efficient loading of DNA nanostructures with intercalating or groove-binding drugs is an important prerequisite for various applications in drug delivery. However, unambiguous verification and quantification of successful drug loading is often rather challenging. In this work, AFM-IR nanospectroscopy is thus employed to directly visualize the loading of DNA origami nanostructures with the photosensitizer methylene blue (MB). Single MB-loaded DNA origami nanostructures can be clearly resolved in high-resolution infrared (IR) maps and the occurrence of MB-specific IR absorption correlates well with the topographic signals of the DNA origami nanostructures. The intensity of the recorded MB absorption bands furthermore scales with the MB concentration used for MB loading. By comparing single- and multilayer DNA origami nanostructures, it is also shown that the IR signal intensity of the loaded MB increases with the thickness of the DNA origami nanostructures. This indicates that also DNA double helices located in the core of bulky 3D DNA origami nanostructures are accessible for MB loading. AFM-IR nanospectroscopy thus has the potential to become an invaluable tool for quantifying drug loading of DNA origami nanostructures and optimizing drug loading protocols.